Light‐Driven Continuous Twist Movements of Microribbons. Issue 7 (15th January 2019) - Zhang, Yifan; Gong, Yanjun; Li, Bo; Ma, Ren‐Min; Che, Yanke; Zhao, Jincai
Abstract: Despite many advances in the development of artificial systems with helical twist motions or deformations, obtaining materials that can undergo continuous twist movements upon an energy input remains a great challenge. In this work, a continuous twist movement of microribbons driven by scanning laser irradiation, a process that a twist generates initially at one end of the microribbon and is continuously transmitted to the other end and then kept twisting, is reported. Key factors to the achievement of this movement are the fabrication of elastic microribbons that possess relatively low elastic modulus and diagonal photoinduced π‐stacking distortion relative to the microribbon long axis. Furthermore, the scanning laser irradiation is required to drive the π‐stacking distortion with the spatiotemporal coordination for the continuous twist movement of microribbons. These findings may be extended to the achievement of other sophisticated continuous movements of microscale systems. Abstract : A continuous twist movement of microribbons driven by scanning laser irradiation is reported. Key factors to the achievement of this movement are the fabrication of elastic microribbons that possess relatively low elastic modulus and diagonal photoinduced π‐stacking distortion relative to the microribbon long axis. These findings may be extended to the achievement of other sophisticated continuous movements of microscale systems.